2012
DOI: 10.3389/fimmu.2012.00059
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition Receptors in HIV Transmission

Abstract: Dendritic cells (DCs), Langerhans cells (LCs), and macrophages are innate immune cells that reside in genital and intestinal mucosal tissues susceptible to HIV-1 infection. These innate cells play distinct roles in initiation of HIV-1 infection and induction of anti-viral immunity. DCs are potent migratory cells that capture HIV-1 and transfer virus to CD4+ T cells in the lymph nodes, whereas LCs have a protective anti-viral function, and macrophages function as viral reservoirs since they produce viruses over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 109 publications
0
11
0
1
Order By: Relevance
“…28,45 It has been suggested that these cells may contribute to HIV-1 entry in penile urethral and vaginal mucosal sites. 28 Furthermore, the cell surface molecule DC-SIGN expressed on DCs has been proposed to be important for binding and transporting HIV-1 from mucosa to regional lymph nodes, 14,16,17 although we find this molecule on macrophages and not DCs.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…28,45 It has been suggested that these cells may contribute to HIV-1 entry in penile urethral and vaginal mucosal sites. 28 Furthermore, the cell surface molecule DC-SIGN expressed on DCs has been proposed to be important for binding and transporting HIV-1 from mucosa to regional lymph nodes, 14,16,17 although we find this molecule on macrophages and not DCs.…”
mentioning
confidence: 54%
“…14,15 Within mucosal tissues, DCs may be among the first cells to encounter HIV-1 and have been hypothesized to play a crucial role in initial virus dissemination by transporting HIV-1 to CD4 + T lymphocytes in regional lymph nodes. 14,16,17 Moreover, DCs and monocyte/macrophages are a key determinant of the activation state of CD4 + T lymphocytes in mucosal tissues. Thus mucosal innate immune function has critical implications for infectious diseases as well as autoimmunity and even systemic immune regulation.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that virus translocates between epithelial cells until susceptible cells are found either in or below the epithelium [3] . Alternatively, Langerhans cells may sample the surface, acquire virus, and move it to areas of abundant target cells [4] , [5] . Finally, transcytosis of HIV-1 (i.e., movement through cells) has been studied as a potential mechanism to translocate virus from mucosal surfaces to deeper-lying CD4+ cells [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…They recognize pathogens through C-type lectin receptor (CLR), Toll-like receptor (TLR), and other pattern recognition receptors [17]. LC express langerin (CD207), a CLR that binds microorganisms for endocytosis, and have Birbeck granules that are involved in endosomal recycling.…”
Section: Langerhans Cells (Lc) Dermal DC (Ddc) and Interdigitatimentioning
confidence: 99%